Business Practices in Small Firms in Developing Countries - McKenzie, David (World Bank, Washington, DC, 2015)
Management has a large effect on the productivity of large firms. But does management matter in micro and small firms, where the majority of the labor force in developing countries works? This study developed 26 questions that measure business practices in marketing, stock-keeping, record-keeping, and financial planning. These questions have been administered in surveys in Bangladesh, Chile, Ghana, Kenya, Mexico, Nigeria, and Sri Lanka. This paper shows that variation in business practices explains as much of the variation in outcomes — sales, profits, and labor productivity and total factor productivity — in microenterprises as in larger enterprises. Panel data from three countries indicate that better business practices predict higher survival rates and faster sales growth. The effect of business practices is robust to including many measures of the owner’s human capital. The analysis finds that owners with higher human capital, children of entrepreneurs, and firms with employees employ better business practices. Competition has less robust effects.